In the Presidium of the Siberian Section of the Academy of Sciences USSR. - Batishchev, V. A. (1960)
On the basis of the resolutinn of the Presidium of Academy of Sciences USSR of 12 December l958, the Forestry Institute of the Academy of Sciences has been transferred from Moskovskaya to Krasnoyarskaya Oblast. The Institute has adopted the title 1"Institute of Forestry and Wood," and it has been included in the system of the Siberian Section of the Academy of Sciences USSR. Transferred to the Institute of Forestry and Wood of the Siberian Section of the Academy of Sciences USSR were the Central Kazakhastan protective forest cultivation station and the Yakutsk larch forests study station of the Institute of Forestry of the Academy of Sciences USSR. The Institute has been entrusted with the methodical guidance of the work of forestry divisions and groups which are located in the cities of Novosibirsk, Irkutsk and the Far-Eastern Affiliate of the Siberian Section of the Academy of Sciences USSR. Trans. of Izvestiya Sibirskogo Otdeleniya Akademii Nauk SSR (Proceedings of the SIberian Section AS USSR), n3,p133-134, November 1959.